Advances in quantum simulations of ATPase catalysis in the myosin motor - Kiani, Farooq Ahmad; Fischer, Stefan (Current opinion in structural biology, 2015)
During its contraction cycle, the myosin motor catalyzes the hydrolysis of ATP. Several combined quantum/classical mechanics (QM/MM) studies of this step have been published, which substantially contributed to our thinking about the catalytic mechanism. The methodological difficulties encountered over the years in the simulation of this complex reaction are now understood: (a) Polarization of the protein peptide groups surrounding the highly charged ATP4− cannot be neglected. (b) Some unsuspected protein groups need to be treated QM. (c) Interactions with the γ-phosphate versus the β-phosphate favor a concurrent versus a sequential mechanism, respectively. Thus, these practical aspects strongly influence the computed mechanism, and should be considered when studying other catalyzed phosphor-ester hydrolysis reactions, such as in ATPases or GTPases.
Gesehen am 15.10.2020